A communicational matrix to the imaginary: Looking into the media imaginary. Issue 1 (1st June 2017) - Mateus, Samuel
Phenomenology, Sociology, Hermeneutics and Psychoanalysis have accumulated different methods and knowledge on the imaginary. Nevertheless, the crucial connection between the social imagining and communication has not always been truly examined. In this article, we take the imaginary (seen as a symbolic thought of images) and communication (seen as a process of symbolic reproduction) as correlated notions, and work upon a communicational matrix of the imaginary. We emphasize three key elements of the imaginary: by pointing to the verbal-iconic, technical and mediatized dimensions we will be paying special attention to the media imaginary and the effects of its commemorative logic to the propagation of public imaginaries.